2021
DOI: 10.1038/s41467-021-20937-7
|View full text |Cite
|
Sign up to set email alerts
|

Extreme temperatures compromise male and female fertility in a large desert bird

Abstract: Temperature has a crucial influence on the places where species can survive and reproduce. Past research has primarily focused on survival, making it unclear if temperature fluctuations constrain reproductive success, and if so whether populations harbour the potential to respond to climatic shifts. Here, using two decades of data from a large experimental breeding programme of the iconic ostrich (Struthio camelus) in South Africa, we show that the number of eggs females laid and the number of sperm males prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 88 publications
2
56
0
Order By: Relevance
“…Female reproduction is also sensitive to temperature, especially because egg maturation and oviposition are two highly temperaturedependent processes (Angilletta, 2009;Berger et al, 2008;Kingsolver & Huey, 2008;Schou et al, 2021), and it is likely that female TSF could be modulated further by pre-and post-fertilization mating interactions. For example, physical harm inflicted via male harassment of females during copulation, or physiological harm mediated via toxic ejaculate compounds (Arnqvist & Rowe, 2005;Dougherty et al, 2017;Parker, 2006), could increase female TSF if TSF is dependent on the condition of the individual and costly thermal buffering mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Female reproduction is also sensitive to temperature, especially because egg maturation and oviposition are two highly temperaturedependent processes (Angilletta, 2009;Berger et al, 2008;Kingsolver & Huey, 2008;Schou et al, 2021), and it is likely that female TSF could be modulated further by pre-and post-fertilization mating interactions. For example, physical harm inflicted via male harassment of females during copulation, or physiological harm mediated via toxic ejaculate compounds (Arnqvist & Rowe, 2005;Dougherty et al, 2017;Parker, 2006), could increase female TSF if TSF is dependent on the condition of the individual and costly thermal buffering mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Despite correlative evidence showing a negative relationship between ambient temperature and laying dates 7 , 9 , there are only limited experimental studies showing that spring temperatures affect the timing of laying directly 8 , 10 . Interestingly, in the sole study, we are aware of that measured the effect of changes in ambient temperature on laying in wild birds, Schou et al 98 identified a critical thermal window in captive ostrich ( Struthio camelus ), for which the rate of egg-laying peaked at 20 °C, dropping by 15% and 18% when temperatures increased and decreased by 5 °C, respectively. However, it is unknown which mechanisms contributed to these results.…”
Section: Discussionmentioning
confidence: 99%
“…We used daily records of temperature and reproductive success of 1277 individuals in experimental breeding pairs in the Klein Karoo region of South Africa over a 21-year period. Here daily temperatures can range from -5 to 45ºC during the breeding period (30). We focus on temperature effects on reproduction, as survival can underestimate how temperature affects fitness (14,30).…”
Section: Main Textmentioning
confidence: 99%
“…Here daily temperatures can range from -5 to 45ºC during the breeding period (30). We focus on temperature effects on reproduction, as survival can underestimate how temperature affects fitness (14,30). We analyze selection on female egg-laying rates as our recent work shows this is a key determinant of reproductive success and is influenced by temperature (30) (Fig.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation